Artificial Intelligence Application in English Writing Class: Students’ Perception and Experiences - Amanda Ramadaniza; Ari Andre Rianyansa (Universitas Islam Negeri Palopo, 2026)
This study aims to examine students’ perceptions and experiences regarding the application of Artificial Intelligence (AI) in writing English classes. A mixed-methods approach was used to conduct this study. The population and sample consisted of students from English Language Education Study Programs at Muhammadiyah University of Bengkulu, UIN Raden Mas Said Surakarta, and IAIN Curup, with a total of 43 students. Questionnaires and interview were used as instrument to address the research questions. Questionnaires were distributed to 43 students, while only 5 students were interviewed. The data were analyzed both quantitatively and qualitatively. For quantitative analysis, the data were analyzed using simple calculations involving percentages and mean values. For the qualitative data, coding methods were employed. Based on the research findings, students generally expressed positive perceptions toward the use of ChatGPT in writing instruction. The results indicate that ChatGPT contributes to students’ interest, motivation, engagement, and confidence in writing activities. Many students also believe that ChatGPT helps improve understanding, organize ideas, and enhance the overall quality of the learning experience. Additionally, some students view ChatGPT as a useful tool to support academic goals and future career development. However, not all students show a strong preference for using ChatGPT over conventional learning methods, as some remain neutral or are unsure of its effectiveness. Overall, although ChatGPT has potential as a tool to support EFL writing instruction, its effectiveness remains dependent on individual students’ preferences and experiences.